Latihan Slow Deep Breathing dan Aromaterapi Lavender terhadap Intensitas Nyeri pada Klien Post Seksio Sesaria - Aprina Aprina; Rovida Hartika; Sunarsih Sunarsih (Politeknik Kesehatan Tanjung Karang, 2018)
The World Health Organization (WHO) sets the standard for the birth of a sexually assault operation in a country to be around 5-15 percent per 1000 births worldwide. Based on Basic Health Research (2013) the level of childbirth sectio caesarea in Indonesia has exceeded the maximum limit of 5-15% WHO standard. The rate of cesarean delivery in Indonesia 15.3% of the 20,591 mothers who gave birth within the last 5 years surveyed from 33 provinces. This cesarean delivery may allow for higher complications than normal delivery. The usual complication is a pain. One of the handling interventions of pain with minimal side effects is nonpharmacological management, such as slow-breathing exercises and lavender aromatherapy. This study aims to determine differences in the intensity of pain in postoperative patients sectio caesarea undertaken slow deep breathing exercise with aromatherapy lavender in RSUD Dr. H. Abdul Moeloek Lampung Province in 2018. This type of research uses a quantitative method using quasi-experimental design with Non-Equivalent Control Group design approach. A technique of sampling using purposive sampling technique as much as 60 respondents, 30 respondents group slow deep breathing and 30 respondents aromatherapy group lavender. The study period began on May 18, 2018, to June 30, 2018, in the Pomegranate Room RSUD Dr. H. Abdul Moeloek Lampung Province. Statistical test using t independent Mann Widney. The results showed that there was a difference of slow deep breathing exercise with lavender aromatherapy on the intensity of pain in patients in post sectio caesarea patients in the Pomegranate Room RSUD Dr. H. Abdul Moeloek Lampung Province Year 2018 (p-value=0.000). Researchers suggest that patients can use lavender aromatherapy to reduce the level of pain postoperative sectio caesarea.